Comparative Analysis of Histamine in Fresh and Processed Fish Sold in Jordanian Market - Sirhan, Ala'; AlRashdan, Yazan; Al-Ebini, Yousef; Hassouneh, Loay; Ghrear, Tamara; Abdulra’uf, Lukman Bola (Jordan Journal of Pharmaceutical Sciences, 2024)
Food poisoning from histamine, a biogenic amine formed due to the decarboxylation of histidine by bacteria in fish and fish products, has become a pivotal concern in food safety. This study measured the concentration of histamine in various fish products available in the Jordanian market, but manufactured in multiple countries, utilizing an Enzyme-Linked Immunosorbent Assay (ELISA). The ELISA kit and the protocol were provided by Veratox for histamine. Approximately 93.69% of the samples tested positive for the presence of histamine, with levels ranging between 0.317 and 230.41 mg/kg. Solely 0.9% of the samples exceeded the maximum permissible level established by the European Union (EU) and only 4.5% of the fish samples were free of histamine. The Principal Component Analysis (PCA) revealed that the type of fish was the most significant source of variability in histamine concentration, explaining 31.2% of the variability. Conversely, the sample weight accounted for the least variability (only 20.2%), implying that it has little or no effect on the concentration of histamine in the fish samples.